2022
DOI: 10.1039/d2ma00619g
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multiple ion substitutions on halide ion migration in perovskite solar cells

Abstract: Lead halide perovskites are mixed electronic-ionic conductors. Ionic mobility is related to device stability; the more favourable ion migration is, the sooner material degradation occurs. The highest efficiency perovskite materials,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Strategies to reduce defects have been proposed, such as additive (or solvent) engineering to reduce bulk defects via controlling crystallization, post-treatment to passivate interfacial defects, , and ion substitution to control ion migration. It was reported that low-defect density perovskite films with high crystal plane orientation were prepared by introducing the presynthesized, intrinsically highly oriented two-dimensional (2D) Dion–Jacobson perovskite of (BDA)­PbI 4 (BDA = 1,4-butanediamine) into the PbI 2 solution as a seed for three-dimensional (3D) perovskite epitaxial growth, which finally demonstrated a PCE of 23.95% . The 2D Ruddlesden–Popper perovskite of (NpMA) 2 PbI 4 (NpMAI = 1-naphthalenemethylammoniumiodide) was introduced into the PbI 2 solution to modulate crystal growth, which led to a PCE as high as 24.37% .…”
mentioning
confidence: 99%
“…Strategies to reduce defects have been proposed, such as additive (or solvent) engineering to reduce bulk defects via controlling crystallization, post-treatment to passivate interfacial defects, , and ion substitution to control ion migration. It was reported that low-defect density perovskite films with high crystal plane orientation were prepared by introducing the presynthesized, intrinsically highly oriented two-dimensional (2D) Dion–Jacobson perovskite of (BDA)­PbI 4 (BDA = 1,4-butanediamine) into the PbI 2 solution as a seed for three-dimensional (3D) perovskite epitaxial growth, which finally demonstrated a PCE of 23.95% . The 2D Ruddlesden–Popper perovskite of (NpMA) 2 PbI 4 (NpMAI = 1-naphthalenemethylammoniumiodide) was introduced into the PbI 2 solution to modulate crystal growth, which led to a PCE as high as 24.37% .…”
mentioning
confidence: 99%
“…In a similar manner, I – migration in PSCs has raised several concerns related to its negative impact on the performance and stability of devices. Due to a low activation energy (0.3–0.5 eV), the movement of I – upon external stimuli (light, temperature, and bias) is typically assigned as the main contributor to the ion migration in Pb-based perovskites, although many reports suggest that the migration of the A-site cation is not negligible. During operation (i.e., under illumination and/or bias), accumulation of mobile ions at the contact interfaces screens the built-in potential and/or facilitates the formation of defects, leading to non-radiative recombination . Ion diffusion to transport layers or electrodes can further cause chemical reactions that are harmful to the performance of the device. To date, the link between ion migration and the stability of TLPSCs remains underexplored; further efforts to unravel the extent of efficiency losses and degradation mediated by ion motion are expected to open up paths toward long-term stability in this class of devices.…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…Because the performance and long-term stability of the tandem solar cells are limited by those of PSCs, it is essential to secure the high quality and stability of the wide-band gap perovskite materials. , Various methods have been proposed to improve the properties of the perovskites: recrystallizing the surface, passivation of surface or grain boundaries, and introducing two-dimensional (2D) mixed phases. These methods are effective, but they require additional processes and precise control of process conditions.…”
Section: Introductionmentioning
confidence: 99%